2016
DOI: 10.1093/hmg/ddw369
|View full text |Cite
|
Sign up to set email alerts
|

Most brain disease-associated and eQTL haplotypes are not located within transcription factor DNase-seq footprints in brain

Abstract: Dense genotyping approaches have revealed much about the genetic architecture both of gene expression and disease susceptibility. However, assigning causality to genetic variants associated with a transcriptomic or phenotypic trait presents a far greater challenge. The development of epigenomic resources by ENCODE, the Epigenomic Roadmap and others has led to strategies that seek to infer the likely functional variants underlying these genome-wide association signals. It is known, for example, that such varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The aggregate models obtain good performance over a relatively wide range of thresholds compared with the models using individual methods. most haplotypes with cis-acting effects on gene expression (eQTLs) contain SNPs that are located within DNase I hypersensitive regions (Handel et al, 2017). However, DHS regions span a large fraction of the genome, and many SNPs within DHS regions have no evidence for influencing gene expression.…”
Section: Footprints Predict Effects Of Genetic Variants On Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aggregate models obtain good performance over a relatively wide range of thresholds compared with the models using individual methods. most haplotypes with cis-acting effects on gene expression (eQTLs) contain SNPs that are located within DNase I hypersensitive regions (Handel et al, 2017). However, DHS regions span a large fraction of the genome, and many SNPs within DHS regions have no evidence for influencing gene expression.…”
Section: Footprints Predict Effects Of Genetic Variants On Gene Expressionmentioning
confidence: 99%
“…However, DHS regions span a large fraction of the genome, and many SNPs within DHS regions have no evidence for influencing gene expression. It remains controversial whether footprints more precisely capture the causal variants on eQTL haplotypes: some recent studies found that only a small fraction of eQTL haplotypes overlap footprints (Handel et al, 2017;Moyerbrailean et al, 2016), whereas others have suggested stronger enrichment (Degner et al, 2012;Schwessinger et al, 2017). To address this question, we examined overlap between footprints in our database with eQTLs from the Genotype-Tissue Expression (GTEx) consortium.…”
Section: Footprints Predict Effects Of Genetic Variants On Gene Expressionmentioning
confidence: 99%
“…However, postmortem brain data are well known to be confounded by cell heterogeneity and environmental factors (Lipska et al, 2006) and do not capture changes at early neurodevelopmental stages (Brennand et al, 2015). Enrichment analyses of GWAS risk variants for SZ and other brain disorders using postmortem brain open chromatin data (DNase I hypersensitive sites [DHSs]) yield inconsistent findings (Schizophrenia Working Group of the Psychiatric Genomics Consortium, 2014; Handel et al, 2017). The lack of open chromatin profiles in appropriate cellular models has thus been a roadblock in interpreting functional noncoding sequences and GWAS risk variants for neuropsychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Although eQTLs are reportedly associated with gene expression ( 35, 36 ), some TF ChIP-seq and DNase-seq studies in humans suggest that more than 50% of eQTLs are not associated with TF binding sites ( 19, 37 ), implying that genomic regulatory features could be used to assess the potential regulatory function of eQTLs. To test this possible use of our Functional Confidence scoring system, we obtained cis-eQTL data from adipose, liver, spleen, hypothalamus, kidney, lung, muscle, and rumen of cattle from the farmGTEx database (https://www.farmgtex.org/).…”
Section: Resultsmentioning
confidence: 99%